Peningkatan Hasil Belajar dan Kemandirian Siswa dengan Metode PBL Pada Materi Sabda Bahagia Fase D SMP Xaverius 1 Bandar Lampung - Yusup Catur Harjanto; Sugiyana, SJ; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
From the teaching experience at Xaverius 1 Junior High School Bandar Lampung, it was found that there was a low learning outcome score of students on the material of the happy word in the learning of Catholic Religious Education Phase D in grade VII which amounted to 26 participants. To improve learning outcomes, it is tried using the PBL model Can the PBL method improve PAK learning outcomes? To determine the effectiveness of PBL for PAK learning outcomes, PTK research was carried out in learning the Happy Word Material, in 2 cycles with the PBL Model, data collection instruments using tests and observations as well as documentation. The research process is carried out through a cycle of class action with stages of planning, implementation, observation, and reflection. The purpose of focusing on the independence dimension is to improve the affective aspect in the learning process. The results of the study showed a significant increase from cycle 1 to cycle 2 in the aspect of learning independence with the Problem Based Learning (PBL) method from 55% to 82%. Meanwhile, in the cognitive aspect, there was an increase in student learning outcomes with the results that proficient 0% to 58%, proficient 35% to 42%, and basic there was a decrease of 14% to 0%, special intervention decreased from 12% to 0%. With an average increase in learning achievement in cycle 1 67 to 88 in cycle 2. Thus, it can be concluded that the application of the PBL model has proven to be effective in improving the learning outcomes of Catholic Religious Education (PAK) and the dimension of student independence.